Exploring the Perspectives of Single Young Women in Jordan on Vaginal Birth and Cesarean Section: A Cross-Sectional Study - Basha, Asma; Al-Hamdan, Zaid; Yousef, Hala; AlJazzazi, Roaa; Nawashi, Qussay; Amairah, Rwand; Ismail, Omar (Journal of Posthumanism, 2025)
Aim: To explore the perceptions, knowledge, and attitude of unmarried Jordanian women towards vaginal birth (VB) and CS, as well as discovering their preference, and their predominant source of information regarding the two modes of birth. Methodology: This is a cross-sectional survey. Data was collected through face-to-face interviews. The questionnaire consists of 30 questions. The study sample included any unmarried Jordanian woman aged between 18 and 25 years who agreed to participate in this study. No married women, or women who had previously been pregnant, were included in the study. Results: A total of 1019 participants were included. Most of the participants agreed that VB was an acceptable mode of delivery. 75% believed that the mother recovers faster after VB. The majority of the single women held a positive perception towards good maternal health after VB. 90.9% held the view that the mother feels happier when seeing her baby soon after VB. 76.2% (n=776) of the participants thought that VB establishes a beautiful emotional connection between the mother and her baby. In addition, 756 (74.2%) women stated that they believed vaginal birth pains to be annoying. Conclusion: Women's choices of delivery mode are related to individual preferences, knowledge, level of education, and socioeconomic status. Findings of this study revealed that single women in Jordan favor VB over CS. For those who showed a preference for CS, that choice was most often based on lack of some knowledge, and/or fear of pain during a VB. The number of clinically unnecessary CS births can be reduced through a concerted effort to improve women’s knowledge, and spreading cultural awareness using targeted mass media to inform young women of the pros and cons of having a VB.